HAK PEREMPUAN HINDU BALI ATAS HARTA WARISAN SUAMI - Suka Asih K. Tus, Desyanti (Institut Hindu Dharma Negeri Denpasar, 2021)
Indonesia does not have a unified regulation regarding inheritance law. This legal pluralism occurs with the application of three different regulations related to inheritance law namely is Western Civil Law, Compilation of Islamic Laws and Customary laws which is applicable based on the region such as Bali Customary Laws. The customary law sourced from the norms, religion, principle that develop within the society. Customary inheritance law is strongly influenced by the family system that applies in every region in Indonesia. Customary inheritance law in Bali is influenced by the patrilineal system adopted in Bali. The patrilineal system adheres to the male line. The patrilineal system places men as the successors of the family including those who are obliged and entitled to family inheritance. This situation makes the position of women as subordinate parties in the family, especially in terms of inheritance. The rights of Hindu women in Bali to her husband's inheritance are often disregarded, forgotten, and abolished. Based on national law, a wife who is left dead by her husband will automatically become an heir. This situation does not necessarily apply to Balinese customary law with the patrilineal system. Social change and demands of the feminist theory have not brought a change to the application of Balinese customary inheritance laws in the community. The presence of provisions in the form of the MUDP (an Indonesia Governmental Body for Balinese) decision and the Supreme Court's decision have not been able to bring a change to the position of women (widows because of death) as husband's heir. The lack of knowledge and legal awareness of Hindu women in Bali over their position as heirs is one of the causes of the weak position of Hindu women in Bali as heirs. This paper will discuss the rights of Hindu women in Bali for husband's inheritance. This paper uses a normative juridical research method.Keywords: Rights of Hindu Women in Bali, Husband's Inheritance